Development of an automated technical drawing plotter for enhanced engineering education / Mohd Arzaimiruddin Ariffin, Ahmad Firdaus Yazid and Muhammad Faiz Mohd Mazelan - Ariffin, Mohd Arzaimiruddin; Yazid, Ahmad Firdaus; Mohd Mazelan, Muhammad Faiz (2024)
Engineering drawing is a fundamental course in the Mechanical Engineering Diploma programme, encompassing both technical drawing and Computer-Aided Design (CAD). However, students at UiTM Cawangan Terengganu Kampus Bukit Besi face significant challenges with traditional hand-drawn techniques. This project aims to develop an automated technical drawing plotter to aid in learning by automatically drawing simple shapes. The methodology is divided into mechanical and electronic components. Mechanical parts, such as the gondola and brackets, are designed following a comprehensive engineering design process and fabricated using 3D printing. The electronic control system is developed using an Arduino UNO circuit board. The plotter successfully draws basic shapes, including diagonals and rectangles, demonstrating its potential as a teaching aid. This project addresses the learning difficulties in technical drawing, offering a practical solution that enhances students' understanding. Future enhancements could expand the plotter’s capabilities to draw more complex shapes and integrate additional educational features.